Courtesy, Cultivation, and the Ethics of Discernment in Book 6 of "The Faerie Queene" - Wiseman, Rebecca L. (The sixteenth century journal, 2016)
Book 6 of Spenser's Faerie Queene examines courtesy's social and moral demands, reframing the conceptual parameters of courtesy by suggesting the courteous performance and aesthetic experience are mutually informing. Although Continental conduct books had long established courtesy as a social expedient, Spenser swerves away from the narrow field of the social by opening courtesy up to the complex demands of the ethical, proposing that courtesy plays a central role in regulating gracious exchange. The Faerie Queens book 6 suggests that courtesy entails perfected aesthetic discernment: an ability to see, judge, and behave properly in a given situation, without hope of reward. Focusing on the courteous engagements and ethical struggles of three characters—Calidore, the Salvage Man, and Colin Clout—I argue that Spenser's epic reveals aesthetic experience to be a central means for virtuous development, a view that would come to be shared by Spenser's poetic successors.